Anti-staphylococcal properties of Eichhornia crassipes, Pistacia vera, and Ziziphus amole leaf extracts: Isolates from cattle and rabbits. (December 2017) - Gutiérrez-Morales, Andrea; Velázquez-Ordoñez, Valente; Khusro, Ameer; Salem, Abdelfattah Z.M.; Estrada-Zúñiga, María Elena; Salem, Mohamed Z.M.; Valladares-Carranza, Benjamin; Burrola-Aguilar, Cristina
Abstract: The desideratum aim of the present context was to assess the biopotency of methanolic extracts of Eichhornia crassipes ( E. crassipes ), Pistacia vera ( P. vera ), and Ziziphus amole ( Z. amole ) leaves against various staphylococcal strains, and to quantify the phenolics as well as saponin content in them. The antibacterial activity of various concentrations (62.5–1000 μg/mL) of plant extracts was tested against control clinical strains ( Staphylococcus aureus ATCC 25923, S. aureus ATCC 29213, and S. aureus ATCC 43300), methicillin-resistant S. aureus (MRSA1 and MRSA2), oxacillin sensitive S. aureus (SOSA1 and SOSA2), and coagulase-negative Staphylococcus epidermidis (CoNS1, CoNS2, and CoNS3) using disc diffusion assay. Leaf extracts of the three plants exhibited pronounced growth inhibitory characteristics against staphylococci in a dose dependent manner. E. crassipes extract depicted the highest relative percentage inhibition values against control clinical strains (68.6 ± 0.5%), while P. vera (68.6 ± 0.3%) and Z. amole (74.79 ± 0.3%) extracts showed pronounced relative inhibition values against staphylococcal strains isolated from cattle. Total phenols and saponin content of leaf extracts were investigated by standard in vitro methods. The methanolic extracts of these plants were found to comprise substantial content of phenolics and saponin at varying levels. The highest value of phenolics was estimated in P. vera extract (60.0 ± 1.3 mg gallic acid/g extract), followed by Z. amole (33.6 ± 1.4 mg gallic acid/g extract), and E. crassipes (23.0 ± 1.3 mg gallic acid/g extract). Saponin content for P. vera, Z. amole, and E. crassipes extracts were estimated as 41.0 ± 1.3, 35.8 ± 1.3, and 25.0 ± 1.2 mg diosgenin/g extract, respectively. The outcome of this study suggested the exploitation of methanolic extract of P. vera, Z. amole, and E. crassipes leaves for their possible application in ethnomedicine, particularly as drugs preparation against staphylococcal infections. In conclusion, the study indicates the biopotency of these plants against pathogenic MRSA present in cattle, and SOSA as well as CoNS bacteria present in rabbits, which could be a serious issue for livestock. Highlights: E. crassipes, P. vera, and Z. amole revealed anti-staphylococcal traits. Methanolic leaf extracts of these plants exhibited pronounced growth inhibitory characteristics. The methanolic extracts comprised substantial content of phenolics and saponins. Application of these plants leaf extract in ethnomedicine has been suggested. The studied plants can be productively used against staphylococcal infections.